Gender differences in nutritional status, diet and physical activity among adolescents in eight countries in sub‐Saharan Africa. Issue 1 (28th November 2019) - Darling, Anne Marie; Sunguya, Bruno; Ismail, Abbas; Manu, Abubakar; Canavan, Chelsey; Assefa, Nega; Sie, Ali; Fawzi, Wafaie; Sudfeld, Chris; Guwattude, David
Abstract: Objective: The objective of this study was to evaluate gender differences in nutritional status, dietary intake, physical activity and hand hygiene among adolescents from diverse geographical settings in sub‐Saharan Africa. Methods: This study utilised cross‐sectional data from six countries (Burkina Faso, Ethiopia, Ghana, Nigeria, Tanzania and Uganda) within the ARISE Adolescent Health Survey ( n  = 7625). Body mass index (BMI) was calculated using measured heights and weights, and z ‐scores were calculated based on the 2007 WHO growth standards for age and sex. Information on demographics, diet and health behaviours was collected through face‐to‐face interviews using a standardised questionnaire. Site‐specific and pooled prevalence ratios were determined. Results: The prevalence of underweight, overweight and stunting pooled across sites was 14.3%, 6.8% and 18.1%, respectively. Female sex was associated with a lower risk of being underweight (pooled prevalence ratio 0.66, 95% 0.57, 0.77) and stunted (pooled PR 0.63, 95% CI 0.55, 0.71), but a higher risk of being overweight (pooled PR 1.60, 95% CI 1.26, 2.06). Females were also less likely to exercise for 1 h or more per day (pooled PR 0.77, 95% CI 0.67, 0.88), and more likely to wash hands after using toilets or latrines and to wash hands with soap (pooled PRs 1.13, 95% CI 1.05, 1.21 and 1.35, 95% CI 1.23, 1.45, respectively). Conclusion: Our results emphasise that sex is a key predictor of nutritional status among sub‐Saharan African adolescents and suggest that gender‐specific interventions may be required to reduce the double burden of under‐ and overnutrition. Abstract : Objectif: L'objectif de cette étude était d'évaluer les différences entre les sexes en matière d'état nutritionnel, d'apport alimentaire, d'activité physique et d'hygiène des mains chez les adolescents de divers contextes géographiques en Afrique subsaharienne. Méthodes: Cette étude a utilisé des données transversales provenant de six pays (Burkina Faso, Ethiopie, Ghana, Nigeria, Tanzanie et Ouganda) dans le cadre de l'enquête sur la santé des adolescents ARISE ( n  = 7.625). L'indice de masse corporelle (IMC) a été calculé à l'aide des mesures de la taille et du poids et les scores z ont été calculés sur la base des normes de croissance de 2007 de l'OMS pour l'âge et le sexe. Les informations sur la démographie, les comportements diététiques et de santé ont été recueillies lors d'entretiens se face à face à l'aide d'un questionnaire standardisé. Les rapports de prévalences poolés et spécifiques au site ont été déterminés. Résultats: La prévalence de l'insuffisance pondérale, du surpoids et du retard de croissance, répartie entre les sites, était de 14, 3%, 6, 8% et 18, 1%, respectivement. Le sexe féminin était associé à un risque plus faible d'avoir une insuffisance pondérale (rapport de prévalence poolée, RP: 0, 66 ; 95%: 0, 57 ‐ 0, 77) et d'avoir un retard de croissance (RP poolé: 0, 63 ; IC95%: 0.55–0.71), mais un risque plus élevé de surpoids (PR poolé: 1.60; IC95%: 1.26–2.06). Les filles étaient également moins susceptibles de faire de l'exercice physique pendant au moins une heure par jour (RP poolé: 0, 77 ; IC95%: 0.67–0.88) et plus susceptibles de se laver les mains après avoir utilisé des toilettes ou des latrines et de se laver les mains au savon (RP poolé: 13.1; IC95%: 1.05–1.21 et 1.35; IC95%: 1.23–1.45 respectivement). Conclusion: Nos résultats soulignent que le sexe est un facteur prédictif de l'état nutritionnel chez les adolescents africains subsahariens et suggèrent que des interventions spécifiques au genre pourraient être nécessaires pour réduire la double charge de la sous‐nutrition et de la suralimentation.